To multiply the binomials \( (2x - 5)(x + 7) \), you can follow these steps in the correct order:
-
Distribute \(2x\) to both terms in the second binomial:
- \(2x \cdot x = 2x^2\)
- \(2x \cdot 7 = 14x\)
-
Distribute \(-5\) to both terms in the second binomial:
- \(-5 \cdot x = -5x\)
- \(-5 \cdot 7 = -35\)
-
Combine all the results from the distributions:
- \(2x^2 + 14x - 5x - 35\)
-
Simplify the expression by combining like terms:
- \(2x^2 + (14x - 5x) - 35 = 2x^2 + 9x - 35\)
Thus, the final simplified trinomial is \(2x^2 + 9x - 35\).